Worms on drugs: ecotoxicological effects of acetylsalicylic acid on the Polychaeta species Hediste diversicolor in terms of biochemical and histological alterations - Gomes, Ana (2022)
Pharmaceuticals are important environmental stressors since they have a worldwide use; they are usually released in the aquatic compartment without adequate treatment, and because of their intrinsic properties, they may affect several non-target organisms. Acetylsalicylic acid (ASA), the active substance of aspirin, is a non-steroidal anti-inflammatory drug, being one of the most widely prescribed analgesics in human medical care. Consequently, this compound is systematically reported to occur in the wild, where it may exert toxic effects on non-target species, which are mostly uncharacterized so far. The objective of the present work was to assess the acute and chronic effects of ASA on selected oxidative stress biomarkers [catalase (CAT), glutathione reductase (GRed), glutathione peroxidase (GPx), glutathione S-transferase (GST)], lipid peroxidation (thiobarbituric acid-reactive substance), and histological alterations in the polychaete Hediste diversicolor (Annelida: Polychaeta). The obtained data showed that ASA is not exempt of toxicity, since it was responsible for significant, albeit transient, changes in biomarkers related to the redox status of the organisms, occurring as an increase in the activity of catalase in the individuals exposed acutely to ASA. Chronic exposure to ecologically relevant concentrations of this drug showed to be mostly ineffective in promoting any significant biochemical alteration in H. diversicolor. However, histochemical observations revealed proliferation of mucous cells in the tegument of chronically exposed individuals to ASA.